THE INFLUENCE OF SELF-EFFICACY, OPTIMISM, HOPE, AND RESILIENCE ON WORK ENGAGEMENT WITH MEDIATOR VARIABLE OF PERCEIVED ORGANIZATIONAL SUPPORT ON LECTURERS OF PUBLIC HIGHER EDUCATION INSTITUTIONS IN SURAKARTA - priyatama, aditya nanda; Zainudin, Muhamad; Handoyo, Seger (Universitas Ahmad Dahlan, 2018)
One of human resources exerting an influence on the process of quality development in higher education institutions is lecturer. Lecturers play a role in realizing the purpose of national education (enhancing intellectual capacity of the life of nation, and developing quality of good and civilized Indonesian people). They can give contribution to higher education institutions if they make effective efforts and act in an appropriate manner (not only in terms of the quantity of efforts, but also the direction of the efforts), maintain good attitudes, attempt or intend to work, are supported by the institution for the sake of their success of performance. For that reason, it is important for lecturers to recognize their responsibility and performance, as well as to measure their efforts according to indicator of success. One way to improve organizational performance is by identifying the extent of lecturersâ work engagement. Several studies have examined such components of work engagement as self-efficacy, optimism, hope, and resilience. The present research is intended to consider several psychological constructs related to self-efficacy, optimism, hope, and resilience which influence work engagement by using mediator variable of perceived organizational support on lecturers of public higher education institutions in Surakarta. Samples include 393 lecturers of Universitas Sebelas Maret Surakarta. Data were analyzed using Structural Equation Modeling (SEM) with the application of Lisrel 8.70 program. The analysis results indicate that 1) the model is considered fit,2)Â Â there is a significant influence of self-efficacy, optimism, hope, and resilience on lecturersâ work engagement, and 3) perceived organization support presents as good mediator to connect the aforementioned variables.